2011
DOI: 10.1111/j.1365-2265.2010.03924.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment in children with idiopathic short stature: correlation of growth response with peripheral thyroid hormone action

Abstract: GH therapy induced individual changes in TR expression in ISS that correlated with their growth response. The basal TR mRNA level could predetermine the change in TR expression and therefore the sensitivity to GH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The authors reported that the higher increase in TRα1 and TRα2 mRNAs levels after 12 months of GH treatment was positively correlated to the gain of growth velocity and bone markers. Moreover, they observed a better gain in growth velocity in response to GH therapy in the individuals who had the higher increase of TRα1 mRNA level [61]. This finding is in line with the main role of TRα1 in bone longitudinal growth and suggests a possible direct influence of GH on thyroid hormone receptors in the growth plate.…”
Section: Gh Impact On Thyroid Hormone Receptorssupporting
confidence: 59%
See 1 more Smart Citation
“…The authors reported that the higher increase in TRα1 and TRα2 mRNAs levels after 12 months of GH treatment was positively correlated to the gain of growth velocity and bone markers. Moreover, they observed a better gain in growth velocity in response to GH therapy in the individuals who had the higher increase of TRα1 mRNA level [61]. This finding is in line with the main role of TRα1 in bone longitudinal growth and suggests a possible direct influence of GH on thyroid hormone receptors in the growth plate.…”
Section: Gh Impact On Thyroid Hormone Receptorssupporting
confidence: 59%
“…The presence of thyroid hormone receptors (TRs) in growth plates is well known [60]. Susperreguy et al [61] reported that the individual growth response in patients with idiopathic short stature treated with rhGH correlated positively with the change in the TRα mRNA level and negatively with the TRβ mRNA level. The design of the study was based on the evaluation of mRNA of TRs in peripheral blood mononuclear cells; however; there was a parallel evaluation of serum sex hormone binding globulin which, reflects the effect of thyroid hormones on the liver, and also osteocalcin and b-cross laps, which are serum biochemical markers reflecting thyroid hormone action at the bone tissue.…”
Section: Gh Impact On Thyroid Hormone Receptorsmentioning
confidence: 99%
“…This FT4 decline was regarded as a reflection of mild central hypothyroidism. Even though the etiology of declining FT4 as result of mild central hypothyroidism and (mild) ESS may not be comparable, we hypothesize that prolonged lowered thyroid hormone concentrations in (non-acutely ill) children with cancer may contribute to adverse late effects, such as short stature, weight gain, dyslipidemia, fatigue or the pathogenesis of early frailty, on childhood cancer survivors [14,[21][22][23]. Therefore, we aim to follow thyroid hormone parameters in relation to these possible adverse late effects until the end of cancer treatment in this large prospective cohort.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mild thyroid insufficiency may diminish tissue sensitivity to growth hormone in normal children [13]. The same occurs in children with DS.…”
mentioning
confidence: 95%